The Phenomenon of Instant Interpretation on TikTok and the Risk of Reducing the Meaning of Al-Quranic Verses among the Younger Generation - Akram, Akram; Djafar, Arinil Hidayah; Rustan, Edhy; Harun, Amrullah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The development of social media, especially TikTok, has encouraged the emergence of the phenomenon of